Dear white woman, please come home - Williams, Kimberlee Yolanda (Tantor Media, Inc., 2023)
Dear White Woman, Please Come Home is Kimberlee Yolanda Williams's invitation to white women longing for authentic friendship with Black and brown women, the kind of friendship with no place for secrets, the kind of relationship where truth-telling is welcome, even when it hurts. The idea for the book was born after attending a workshop that left her shaken and angry. In it, Kimberlee listened as white woman after white woman didn't understand how this or that comment, custom, behavior, or norm so negatively impacted women of color. Eventually she had an epiphany: How could white women know what we (Black and brown women) go through if we don't tell them? In the resulting book she explores with vulnerability, sorrow, rage, and humor how white women, often despite best intentions, signal to her and other women of color to proceed with caution when in their presence. The letters' story arc, combined with end-of-chapter questions for deep reflection, offer white women insight to the damage done as well as to what it takes to "come home," to be trusted. The question throughout the book lingers until the very last letter: Will Kimberlee find her long lost "sister"? Will she want to "come home"? Be ready to "come home"?